The long journey of Gracia Mendes - Birnbaum, Marianna D. (Central European University Press, 2003)
"Gracia Mendes was a sixteenth-century entrepreneur and one of the wealthiest women in Europe, who, while a practicing Christian, remained for much of her life a secret Jew." "The biography examines her rise to power in the face of immense obstacles - political, religious, economic, and social." "Gracia was born in 1510 in Portugal. At the age of eighteen, she married Francisco Mendes, a successful Jewish spice trader. After her husband's death in 1536 and in response to the religious persecutions of the day, she moved her family from Portugal. Her travels led her through Antwerp, Venice, Ferrara, Ragusa and finally to Constantinople, from where the Ottoman Empire dominated the territories of former Byzantium and offered shelter for the battered Conversos (converted Jews)." "After her arrival in 1553, she became the most prominent businesswoman of the community and a patron of Jewish causes. Her life exemplifies the perseverance of the Jewish culture to survive and triumph even in extremely adverse conditions."--Jacket.